Using Mathcad in electromagnetics education - DeLyser, R.R. (IEEE transactions on education, 1996)
Mathcad is an effective learning tool in electromagnetics courses. Use of Mathcad by students in such courses at the University of Denver incorporate four essential ingredients needed for the successful integration of computer aided learning into a curriculum component: (1) involvement by the student in establishing what is to be analyzed by the computer; (2) a general purpose tool rather than concept-specific software; (3) a user friendly interface; and (4) effective integration of the computational tool(s) into the course. This paper gives examples of the use of Mathcad in the subject areas of electrostatics, plane wave propagation, transmission lines, antennas, and advanced topics.